Efeito da escovação e das bebidas na rugosidade superficial de bráquetes cerâmicos - Oliveira, Cibele Braga De; Gandini JÚnior, Luiz Gonzaga; Santos-pinto, Ary (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
AbstractIntroductionWhen introduced into the oral environment, the ceramic brackets may undergo change their structure caused by the process of chemical and mechanical degradation of the material.ObjectiveThis study evaluated the surface roughness of ceramic brackets and whether it is altered by toothbrushing process and diet solutions.Material and methodSeven ceramic brackets of four commercial brands were tested: two monocrystalline and two polycrystalline. The brackets were immersed in solutions of coffee, red wine, Coke, black tea and artificial saliva for 21 days. Another group of brackets of each brand were also immersed in the same solutions and for an equal time, but with daily brushing performed by a toothbrushing machine. The surface roughness (Ra) was analyzed by a Roughness Tester (Surftest SJ–400,Mitutoyo®) before and after 24 hours, 7, 14 and 21 days. The data were evaluated by the Analysis of Multivariate Profiles, Analysis of Variance (ANOVA), multiple comparison test of means.ResultThe results of Ra and its change after 21 days were: Ra mean of Allure = 0.277μm (change = 0.002μm), Inspire Ice = 0.262μm (change = 0.013μm), Radiance = 0.177μm change = 0.009μm), Transcend = 0.367μm (change = 0.019μm).Conclusionthe surface roughness of the ceramic brackets increased after 21 days of immersion in the solutions, and the immersion time was a significant factor. However, this change in the surface roughness was similar for the monocrystalline and polycrystalline brackets, as well as for the different solutions. Brushing did not change the surface roughness of ceramic brackets.

ResumoIntroduçãoQuando introduzidos no meio bucal, os bráquetes cerâmicos podem sofrer alterações em sua estrutura provocadas pelo processo de degradação química e mecânica do material.ObjetivoEste estudo avaliou a rugosidade superficial de bráquetes cerâmicos e se eles sofreram alteração com a escovação dentária e a imersão em bebidas com diferentes pH.Material e métodoForam testados sete bráquetes cerâmicos de incisivo central superior direito de quatro marcas comerciais (duas marcas de bráquete monocristalino e duas de policristalino). Os bráquetes foram imersos em soluções de café, vinho tinto, Coca-Cola, chá preto e saliva artificial durante 21 dias. Outros sete bráquetes de cada marca comercial foram imersos nas mesmas soluções e no mesmo tempo, porém com intervalos de escovação diários realizados por uma máquina de escovação. A rugosidade (Ra) foi obtida por meio de um rugosímetro (Surftest SJ-400, Mitutoyo®) antes e após 24 horas, 7, 14 e 21 dias. Os dados foram avaliados pela análise de perfis multivariados, análise de variância (ANOVA) e teste de comparação múltipla de médias.ResultadoOs resultados da rugosidade e de sua alteração após 21 dias foram: média Ra do Allure = 0,277 μm (alteração = 0,002 μm), Inspire Ice = 0,262 μm (alteração = 0,013 μm), Radiance = 0,177 μm (alteração = 0,009 μm) e Transcend = 0,367 μm (alteração = 0,019 μm).ConclusãoA rugosidade superficial dos bráquetes cerâmicos aumentou após 21 dias de imersão nas soluções, sendo o tempo de imersão um fator significante. No entanto, essa alteração da rugosidade no tempo é semelhante nos bráquetes monocristalinos e policristalinos, assim como nas diferentes soluções. A escovação dentária não produziu alteração na rugosidade superficial de bráquetes cerâmicos.
Effect of brushing and beverages on surface roughness of ceramic brackets
Keywords: Surface properties; orthodontic brackets; toothbrushing; food coloring agents; Propriedades de superfície; suportes ortodônticos; escovação dentária; agentes corantes alimentares